2015
DOI: 10.1080/09540962.2015.1007705
|View full text |Cite
|
Sign up to set email alerts
|

The rhetoric and reality of SME-friendly procurement

Abstract: SME-friendly policies are central to public procurement. The extent to which these policies have been put into practice has gone largely untested, particularly from a SME perspective. To address this gap a survey of SMEs' reported experiences of policy implementation was conducted. Ireland served as the research context. The findings indicate that policy implementation has been limited. Firm size is found to be a significant predictor of SMEs' experiences, with microenterprises more negative than small or medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…From an entrepreneurial policy perspective, public procurement is a means to promote SMEs’ performance and to strengthen their role in the economy and in creating new jobs. However, much of the policy discussions have remained mostly, if not wholly rhetorical, and the implementation of policy ideas on various aspects and levels of public procurement has been only partial and slow (Flynn and Davis, 2015; Loader, 2013). We here reflect what our empirical analysis could add to the growing ‘knowledge base’ of supporting SMEs through public procurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an entrepreneurial policy perspective, public procurement is a means to promote SMEs’ performance and to strengthen their role in the economy and in creating new jobs. However, much of the policy discussions have remained mostly, if not wholly rhetorical, and the implementation of policy ideas on various aspects and levels of public procurement has been only partial and slow (Flynn and Davis, 2015; Loader, 2013). We here reflect what our empirical analysis could add to the growing ‘knowledge base’ of supporting SMEs through public procurement.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that SMEs are underpresented in awarded public tenders (GHK, 2010) and many studies point to barriers, either perceived or actual, that impede SMEs access to public sector markets (e.g. Bovis, 1998; Flynn and Davis, 2015; Flynn et al., 2015; Karjalainen and Kemppainen, 2008; Loader, 2005, 2013; Pickernell et al., 2013; Uyarra et al., 2014). Since transparency, openness and fairness are central principles in public procurement (European Commission, 2015), but public procurers seem to lack clear objectives and priorities for encouraging and supporting SMEs (Loader, 2013), there is an urgent need for investigations on the factors and characteristics that influence SMEs involvement in public procurement.…”
Section: Introductionmentioning
confidence: 99%
“…They are less likely to mentor and support small businesses than budget holders for whom the contract is being let (McKevitt & Davis, ), and poor data on suppliers impedes targeted improvements (Loader, ). A survey conducted in Ireland found that, despite the existence of government policy to encourage increased engagement of small businesses in public contracts, there is limited evidence of successful implementation of this policy (Flynn & Davis, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, there is also evidence of the inability to implement SMEfriendly procurement policies in impactful ways (e.g. Kidalov and Snider, 2011;Flynn and Davis, 2015). This is due to tensions between different objectives of public buyers (e.g.…”
Section: Public Procurement and Small Business Developmentmentioning
confidence: 99%